Epidermal growth factor receptor variant III-mesothelin fusions and methods of using the same - HANSON WILLIAM G; LAUER PETER M (2018)
Provided herein are compositions and methods for eliciting an immune response in a subject. In particular, the present disclosure is directed to fusion proteins comprising an epidermal growth factor receptor variant III (EGFRvIII) polypeptide and a mesothelin polypeptide, and methods of eliciting an immune response using host cells comprising nucleic acid molecules encoding said fusion proteins. In some embodiments, the nucleic acid molecules can encode an EGFRvIII-mesothelin fusion protein comprising an amino acid sequence that is at least i) 90% identical, ii) 95% identical, or iii) 99% identical to EGFRvIIIx5-mesothelin35-622 as set forth in SEQ ID NO:8. 本文提供了用于引发受试者中的免疫响应的组合物和方法。具体地，本公开涉及包含表皮生长因子受体变体III(EGFRvIII)多肽和间皮素多肽的融合蛋白以及使用包含编码该融合蛋白的核酸分子的宿主细胞引发免疫响应的方法。在些实施方式中，所述核酸分子可编码EGFRvIII-间皮素融合蛋白，该融合蛋白包含与如SEQ ID NO:8中所述的EGFRvIIIx5-间皮素35-622具有至少i)90％同性、ii)95％同性或iii)99％同性的氨基酸序列。